Apigeninidin chloride disrupts Toxoplasma gondii Mitochondrial membrane potential and induce reactive oxygen species and metabolites production - Moon, Miya Janelle; Kamasah, Japhet Senyo; Sharma, Homa Nath; Robertson, Boakai K.; Abugri, Daniel A. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionApigeninidin chloride (APi) is a form of 3-deoxyanthrocyanidins (3-DAs) abundantly produced by the red Sorghum bicolor plant. It has been previously reported to be effective against Toxoplasma gondii (T. gondii) tachyzoites grown in vitro with less cytotoxic effect. However, its possible mechanism(s) of action has not been elucidated. Biochemically, we discovered that APi induced high reactive oxygen species (ROS) and mitochondria superoxide (MitoSOX) productions in tachyzoites, leading to mitochondrial membrane potential (MMP) disruption in vitro.MethodsTo confirm our biochemical results at the molecular level, we performed a liquid chromatography-mass spectrometry (LC-MS) analysis on APi-treated parasites to assess any metabolite and lipid alterations often associated with high ROS/MitoSOX production in cells. ResultsNoteworthy is that we detected several important oxidative stress-induced metabolites such as hexanal, aldehydes, methyl undeo10-enoate, butadiynyl phenyl ketone, 16-hydroxyhexadecanoic acid (16-OH, 16:0), 2-hydroxytricosanoic acid (C23:0; O), 3-oxodecanosanoic acid (C22:1; O), 2-hydroxypropylsterate, and furan fatty acids F6 (19FU-FA). DiscussionThese metabolites are associated with lipid, protein, and nucleic acid disruptions. Using atovaquone (Atov) as a control, we observed that it disrupted intracellular tachyzoites’ mitochondrial membrane potential, increased ROS and MitoSOX production, and altered metabolite and lipid production similar to what was observed with our experimental compound APi. Overall, our results indicated that APi targets T. gondii tachyzoite growth through inducing oxidative stress, mitochondrial dysfunction, and eventually parasite death.